Penerapan Hubungan Industrial Terhadap Para Pemuda Desa Modongan, Kecamatan Sooko, Kabupaten Mojokerto - Novita Anggraini; Cucu Irma Firnanda; Salsaliya Eka Faizha; Helmi Varifqi; Annisa Aprilia W; Riza Dwi Ervina; Mentrik Hesti M (Universitas Maritim AMNI Semarang, 2023)
Youth is a valuable asset for the nation's successor. Young people who have entered the world of work. The purpose of carrying out this community service is to provide knowledge or add broader insight to the Modongan village youth regarding the application of work relations in the industrial world. Industry is one of the efforts to improve the welfare of the population. In addition, industrialization is also inseparable from efforts to improve the quality of human resources and the ability to optimally utilize natural resources. In industrial relations there are also labor relations disputes that occur within a company. We tell the village youth that in the industrial world there are institutions that deal with labor relations disputes. Community service activities must also pay attention to aspects of education and training for young people. The importance of providing access to them to acquire the knowledge and skills needed in the world of work, so that they can become productive, independent workers while understanding their rights.